2017
DOI: 10.1371/journal.pone.0171334
|View full text |Cite
|
Sign up to set email alerts
|

Obesity paradox in stroke – Myth or reality? A systematic review

Abstract: Background and purposeBoth stroke and obesity show an increasing incidence worldwide. While obesity is an established risk factor for stroke, its influence on outcome in ischemic stroke is less clear. Many studies suggest a better prognosis in obese patients after stroke (“obesity paradox”). This review aims at assessing the clinical outcomes of obese patients after stroke by performing a systematic literature search.MethodsThe reviewers searched MEDLINE from inception to December 2015. Studies were eligible i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
133
3
7

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 135 publications
(151 citation statements)
references
References 55 publications
8
133
3
7
Order By: Relevance
“…Similar findings were observed in other studies, such as in the Telemedical Project for Integrative Stroke Care (TEMPiS) trial [8]. On the other hand, other investigators showed results contradicting the latter with no improved outcomes in overweight or obese patients [10-14]. A recent meta-analysis including 25 studies and around 300,000 patients found that there was no obesity paradox in patients receiving intravenous thrombolysis [14].…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…Similar findings were observed in other studies, such as in the Telemedical Project for Integrative Stroke Care (TEMPiS) trial [8]. On the other hand, other investigators showed results contradicting the latter with no improved outcomes in overweight or obese patients [10-14]. A recent meta-analysis including 25 studies and around 300,000 patients found that there was no obesity paradox in patients receiving intravenous thrombolysis [14].…”
Section: Discussionsupporting
confidence: 80%
“…On the other hand, other investigators showed results contradicting the latter with no improved outcomes in overweight or obese patients [10-14]. A recent meta-analysis including 25 studies and around 300,000 patients found that there was no obesity paradox in patients receiving intravenous thrombolysis [14]. The authors identified several methodological/design concerns that may have led some investigators to conclude that overweight and obesity were associated with better outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations